2013
DOI: 10.1007/s12042-013-9126-0
|View full text |Cite
|
Sign up to set email alerts
|

Different Molecular Mechanisms Account for Drought Tolerance in Coffea canephora var. Conilon

Abstract: The effects of water deficit on photochemical parameters and expression of several candidate genes were investigated in drought-tolerant clone 73 of Coffea canephora submitted to slowly imposed water limitation. Under irrigation, this clone showed low values of stomatal conductance (g s) and of CO 2 assimilation rates (A) suggesting that it had a great efficiency in controlling stomatal closure and transpiration. After water withdrawal, this clone reached a −3.0 MPa after 15 days without irrigation and showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 40 publications
(59 reference statements)
1
28
0
3
Order By: Relevance
“…The increased transcriptional activity of CcGolS1 under moderate and (particularly) severe stress was greater in D T leaves compared to D S leaves. Vieira et al (2013) have also observed different regulatory responses to drought stress in D T plants.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The increased transcriptional activity of CcGolS1 under moderate and (particularly) severe stress was greater in D T leaves compared to D S leaves. Vieira et al (2013) have also observed different regulatory responses to drought stress in D T plants.…”
Section: Discussionmentioning
confidence: 94%
“…The drought stress experiment was done at the Agronomic Institute of Paraná (IAPAR – latitude 23°18′ S, longitude 51°09′ O, average altitude 585 m; Londrina, Paraná State, Brazil). Two C. canephora clones, D T (clone 14) and D S (clone 109A), with contrasting responses to water deficit stress ( DaMatta et al , 2003 ; Pinheiro et al , 2004 ; Marraccini et al , 2012 ; Vieira et al , 2013 ) were obtained from the Espírito Santo State Institute of Research, Technical Assistance and Rural Extension (Incaper, Brazil) and grown under greenhouse conditions. The experiments were done twice with four biological replicates per experiment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, many climate related experimental studies on coffee plants have focused on the effects of reduced water availability on coffee physiology, gene expression, and biochemical composition. For example, Marraccini et al (2012) and Vieira et al (2013) compared variations in the physiological and gene expression responses of drought tolerant and drought sensitive Robusta varieties, and suggested that the drought tolerant clones had subtle differences in ABA signaling and a better induction of the coffee antioxidant and osmoprotection systems. In another examination of the physiological effects induced by drought, (Menezes-Silva et al 2017) explored the effect of repeated rounds of water deficit and recovery on one Robusta variety.…”
Section: Introductionmentioning
confidence: 99%
“…Dentre os genes avaliados, está presente a Dehidrina, que foi encontrada em bibliotecas de cDNA tanto de folha quanto de fruto (Vieira et al, 2013;Mondego et al, 2011). As…”
unclassified